Search for the decay J/ψ→γ+invisible - Insler, J; Muramatsu, H; Park, C; Thorndike, E; Yang, F; Ricciardi, S; Thomas, C; Artuso, M; Blusk, S; Khalil, S; Mountain, R; Skwarnicki, T; et al. (2010)
A search for J/ψ radiative decay to weakly interacting neutral final states was performed using the CLEO-c detector at the Cornell Electron Storage Ring. J/ψ events were selected by observing the hadronic decay ψ(2S)→π+π-J/ψ. A total of 3.7×106 J/ψ events were used to study the decay J/ψ→γ+X, where X is a narrow state that is invisible to the detector. No significant signal was observed, and upper limits on the branching fraction were set for masses mX up to 960MeV/c2. The upper limit corresponding to mX=0 is 4.3×10-6 at the 90% confidence level. © 2010 The American Physical Society.